Excellent Combination of Tensile ductility and strength due to nanotwinning and a biamodal structure in cryorolled austenitic stainless steel - Kumar, G.Venkata Sarath; Mangipudi, K. R.; Sastry, G.V. S.; Singh, Lalit Kumar; Dhanasekaran, S.; Sivaprasad, K. (Nature Research, 2020)
Austenitic stainless steels are prominent materials for their superior corrosion resistance and a combination of strength and ductility. However, the relatively low yield strength limits its application in high strength structural applications. Cryorolling is one of the promising methods of enhancing the mechanical properties of sheet metals. In the present work, Cryorolling of UNS S31000 stainless steel resulted in five-fold enhancement in yield strength with a significant loss in ductility. However, flash annealing at 800 °C for 120 s could restore its ductility up to 50% of its original ductility. The enhancement in strength is attributed to the formation of deformation nano-twins during flash annealing along with a bimodal grain structure.
Keywords: Excellent Combination; Tensile ductility; Nanotwinning and a biamodal structure; Cryorolled austenitic stainless steel